How aligned are the perspectives of EU regulators and HTA bodies? A comparative analysis of regulatory‐HTA parallel scientific advice. (1st July 2016) - Tafuri, Giovanni; Pagnini, Margherita; Moseley, Jane; Massari, Marco; Petavy, Frank; Behring, Antje; Catalan, Arantxa; Gajraj, Elangovan; Hedberg, Niklas; Obach, Mercè; Osipenko, Leeza; Russo, Pierluigi; et al.
Abstract : Background: In 2010, the European Medicines Agency (EMA) initiated a pilot project on parallel scientific advice with Health Technology Assessment bodies (HTABs) that allows manufacturers to receive simultaneous feedback from both the European Union (EU) regulators and HTABs on their development plans for medicines. Aims: The present retrospective qualitative analysis aimed to explore how the parallel scientific advice system is working and levels of commonality between the EU regulators and HTABs, and among HTABs, when applicants obtain parallel scientific advice from both a regulatory and an HTA perspective. Methods: We analysed the minutes of discussion meetings held at the EMA between 2010, when parallel advice was launched, and 1 May 2015, when the cutoff date for data extraction was set. The analysis was based on predefined criteria and conducted at two different levels of comparison: the answers of the HTABs vs. those of the regulators, and between the answers of the participating HTA agencies. Results: The analysis was based on 31 procedures of parallel scientific advice. The level of full agreements was highest for questions on patient population (77%), while disagreements reached a peak for questions on the study comparator (30%). With regard to comparisons among HTABs, there was a high level of agreement for all domains. Conclusions: There is evident commonality, in terms of evidence requirements between the EU regulators and participating HTABs, as well as among HTABs, on most aspects of clinical development. Indeed, regardless of the question content, the analysis showed that a high level of overall agreement was reached through the process of parallel scientific advice.